Acute isolated internuclear ophthamoplegia. MRI findings - Krapf, H; Schmidt, F; Siekmann, R; Friese, S; Küker, W (2000)
Internuclear ophthalmoplegia is the most frequent supranuclear form of gaze paresis. It is caused by a lesion of the median longitudinal fascicle, which connects the nuclei of the IIIrd and VIth cranial nerves. An acute, isolated onset of this syndrome is highly suggestive of an inflammation of the central nervous system, mostly of multiple sclerosis. We report clinical and imaging findings of a patient with acute onset of internuclear ophthalmoplegia, in whom an isolated infarction of the median longitudinal fascicle in the midbrain could be demonstrated by diffusion-weighted MRI.